Volumetric Oxygen Mass Transfer Coefficient and Surface Tension in Simulated Salt Bioremediation Media. Issue 3 (4th February 2014) - Souza, Ellen Cristina; Moraes, Dante Augusto; Vessoni‐Penna, Thereza Christina; Converti, Attilio; Oliveira, Ricardo Pinheiro de Souza
Abstract Toluene can be removed from contaminated sites via bioremediation through the addition of biosurfactant compounds, which reduce the surface tension. However, aeration and mixing must be optimized to ensure an effective volumetric oxygen mass transfer coefficient (kLa). Experiments were perfomed with different salt containing solutions, which were tested either as such, or with different supplements. kLa values obtained at different agitation intensities and aeration rates were compared with those in water, and correlated with power number and superficial gas velocity. Surface tension decreased when surfactin was added to toluene‐containing media. The seawater‐simulating medium exhibited the highest surface tension reduction.